Theoretical and practical significance of scientific research by The Institute of Public Health of the NAMS of Ukraine (Environment & Health, 2023)
Objective: analytical study of scientific achievements by Institute's specialists in the field of prevention of non-communicable and infectious diseases of the population caused by negative impact of environmental and social factors of living conditions, based on the results of research work and their implementation.Materials and methods: scientific reports, acts of implementation of the results of scientific research works. The research uses a system-analytical method.Research results: The results of research conducted at the Institute for the last three years were analyzed. The physical, chemical, and social factors, life conditions of different segments of the population have been assessed and their negative impact on health has been proven. A number of scientifically substantiated regulatory and methodological instructive and information documents have been developed aimed at minimizing harmful environmental factors and preventing diseases in the population.
Keywords: health care; public health; scientific research; normative and methodological documents